Inclusion of Organic Acids in the Drinking Water and Feed for the Control of Salmonella Heidelberg in Broilers - Ferreira, Taisa Santiago [UNESP]; Ravetti, R.; Rubio, M. S. [UNESP]; Alves, L. B.R. [UNESP]; Saraiva, M. M.S. [UNESP]; Benevides, V. P. [UNESP]; Lima, T. S. [UNESP]; Lima, B. N. [UNESP]; Almeida, A. M. [UNESP]; Berchieri, A. [UNESP] (FapUNIFESP (SciELO), 2022)
Poultry products may be a source of foodborne human salmonellosis. The use of alternatives to antimicrobials that are not harmful to humans may reduce the presence of Salmonella spp. in poultry production. Among the products used, organic acids stand out. In the present study, three different organic acid (OA) blends were evaluated for the control of Salmonella Heidelberg (SH) in commercial broilers. Day-old chicks (n = 114) were randomly assigned to four treatments, with three replicates of 12 birds each. Birds in treatments A and B received SCFA (0.2mL/L) and SCFA + MCFA (0.2mL/L), respectively, in the drinking water, while birds in treatment C received SCFA + MCFA in the feed (2g/Kg of feed). Birds from treatment D did not receive OAs (control group). At 8 days of age, each bird was orally inoculated with SH at 108 CFU/mL, and cloacal swabs and SH enumeration of the cecal content were performed 24-, 48-, and 72-hours post-inoculation (hpi). The results show a reduction of both SH shedding and counts in the birds fed OAs at all pi times relative to the control birds. Fecal shedding was significantly lower in the OA-treated groups compared with the control group. As for SH presence in the cecum, significant differences were detected between groups C and D at 24 and 72 hpi, and between groups B and D at 72 hpi. The results of this study indicate that the use of feeding OAs to broilers may contribute to reduce the incidence of SH in the poultry production chain, allowing better flock health management, provided an efficient biosecurity program is employed.
Keywords: Acidifying agent; Additives; Antimicrobials; Salmonellosis